Unhiding Eros: : The phenomenological approach in the analysis of «erotic tension», the Self-portrait montage, inspired by Heiner Müller’s Description of a painting - Loayza Cabezas, Grimanesa Madeleine (2023)
The phenomenological reflection explains the complexity of the evolution of the constant flow that is scenic poiesis (productive and expectational), as a mobile and mutable phenomenon. As a methodological approach, the formal structures of the phenomenological theory proposed by Sokolowski (2012) describe and analyze the poetic devices of the montage "Description of a painting", focusing on the "erotic tension" that keeps alive the atavistic rhythm of the actor/spectator encounter. In this way, new tools and procedures are incorporated that highlight the multiplicity that theatrical praxis articulates and propose new ways of accessing knowledge that considers the specific circumstances of the epistemic subject, in accordance with contemporary epistemology.